(untitled) (International Journal of Built Environment and Sustainability, 2025)
Water, as an indispensable aspect of life, holds significant importance in ecological, biological, sociological, cultural, and various other perspectives. Humans have always tended to settle near water sources, and water has played a critical role in the development and evolution of human civilization. This article investigates the historical and cultural significance of water, with a specific focus on the ’Bächle’ water canal system in the German city of Freiburg. Examining the relationship between water and urban development, this research discusses how water infrastructure can serve as both a cultural symbol and a fundamental element of a city. At the same time, it emphasizes the role of Bächle in preserving Freiburg’s cultural heritage and enhancing urban sustainability. Originating as a practical infrastructure component for irrigation and waste disposal in the 12th century, Bächle has transformed into a symbol shaping the city’s identity and it cultivates a unique urban experience over time. Beyond its initial function, Bächle contributes to the city’s livability, serving as a source of recreation and functioning as a communal space for social interactions. In this context, through an interdisciplinary approach, the research integrates historical analysis, urban planning perspectives, and cultural studies to unravel the multifaceted layers of Bächle’s impact on Freiburg’s past, present, and future. The research explores how Bächle not only contributes to the practical aspects of urban infrastructure but also plays an important role in improving the quality of life and sustaining the cultural identity of the community. The lessons learned from the Bächle’s legacy offer valuable insights into creating resilient and culturally vibrant urban spaces for future generations.